Financial Free in the Retirement Period by Saving on Stocks - Glenn Brillian Putra Herman Fernando; Agung Prabowo (Research Collaboration Community (RCC), 2020)
This study aims to calculate the minimum estimate of saving stocks per month to be financially free after 30 years of investing in stocks. The research method used is a quantitative method. The results showed that the estimated minimum funds to get passive income of 5 million, which is equivalent for the next 30 years, is IDR 930,936 per month.